The Relationship Between Student’s Personal Hygiene Behavior and Scabies Prevalence in Islamic Boarding School - Anggina, Dientyah Nur; Prameswarie, Thia (Universitas Tribhuwana Tunggadewi, 2024)
Sarcoptes scabiei, a variant of the hominid mite, is the cause of scabies, a skin infestation. In Indonesia, scabies accounted for three of the top 12 skin infestations. Scabies infections are particularly common in islamic boarding schools largely due to poor personal hygiene, which increases the risk of the students being infected. This study aimed to determine the relationship between personal hygiene and the prevalence of scabies. A total of 184 samples that met the inclusion and exclusion criteria were obtained for this study using a cross-sectional method and purposive sampling. Fisher’s exact test and Chi-square analysis were performed on the data. The results showed that the prevalence of scabies is 28.8%. The findings indicate a significant relationship between the prevalence of scabies and showering behavior (p=0.002), hand and nail hygiene (p=0.006), and bedding hygiene (p=0.013). However, no correlation was found between the prevalence of scabies and clothing hygiene (p=0.931). When considering overall showering habits, hand and nail hygiene, and bedding hygiene, there was a significant correlation between student hygiene and scabies prevalence (p=0.030). Islamic boarding schools could address this issue by promoting clean and healthy living habits, imposing sanctions for violations, and cooperating with health facilities to carry out periodic treatment for students suffering from scabies.